ASSESSMENT OF THE IMPACT OF PLANT BASED MEAT ALTERNATIVES ON CONSUMER HEALTH & ENVIRONMENT - Misbah Mahtab, Madiha Rohi, Rashida Perveen, Tabeen Irfan, Noor Ul Ain Shah; Rameen Zahra, Sadaf Javaria, Muhammad Suleman Najib, Muhammad Ali (Chelonian Research Foundation, 2024)
The increased scrutiny of meat production and consumption practices, primarily in Western societies, has resulted in growing awareness regarding the environmental and health implications associated with these practices. Meat production, despite being a significant contributor to global greenhouse gas emissions and utilizing vast land resources, provides less than 20% of total calories and 40% of protein.This study examines the nutritional, consumer, and environmental aspects of plant-based meat alternatives (PBMAs). It highlights the emergence of innovative substitutes, such as fungal-based mycoproteins, which exhibit promising nutritional profiles and reduced environmental footprints compared to conventional meat. Further, it investigates the nutritional differences between PBMAs and traditional meat products, revealing significant variations in protein content, amino acid concentrations, and bioavailability. The research objectives encompass nutritional comparison, consumer perception, and environmental sustainability. By providing comprehensive insights into the evolving landscape of alternative protein sources, the study informs stakeholders and guides decision-making in food production and consumption, contributing to the broader discourse on sustainability and health-conscious diets. Keywords: Mycoprotein, consumer perception, nutritional profile, Meat Substitutes, Dietary Trends